On Decent Work: The Concept Formation - Baylos Grau, Antonio (2016)
This article develops the historical process of the formation of the concept of decent work, its basic guidelines and as its content has been altered by the increasing globalization of the market and the globalization of labor rights. Finally, after analyzing the notion of decent work from different perspectives, the author focus on the cumulative perspective and develop its content.